2002
DOI: 10.1038/415541a
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cγ1 is a physiological guanine nucleotide exchange factor for the nuclear GTPase PIKE

Abstract: Phospholipase C gamma 1 (PLC-gamma 1) hydrolyses phosphatidylinositol-4,5-bisphosphate to the second messengers inositol-1,4,5-trisphosphate and diacylglycerol. PLC-gamma 1 also has mitogenic activity upon growth-factor-dependent tyrosine phosphorylation; however, this activity is not dependent on the phospholipase activity of PLC-gamma 1, but requires an SH3 domain. Here, we demonstrate that PLC-gamma 1 acts as a guanine nucleotide exchange factor (GEF) for PIKE (phosphatidylinositol-3-OH kinase (PI(3)K) enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 26 publications
4
124
1
Order By: Relevance
“…However, PIKE has been described for more than a decade to be present exclusively in neuronal cells and is activated by nerve growth factor-induced neuronal cell proliferation. 34,35 In the present study, we found that PIKE is highly expressed in SCC cells and mediates EGFR-dependent SCC cell proliferation. RESULTS PIKE is highly expressed in human SCC cells but at a low level in normal human keratinocytes The SH3 domain of PLC-g1 has been found to activate nuclear PIKE that activates nuclear class Ia PI3K, which in turn, triggers signaling cascades mediating neuronal cell proliferation.…”
Section: Introductionsupporting
confidence: 51%
“…However, PIKE has been described for more than a decade to be present exclusively in neuronal cells and is activated by nerve growth factor-induced neuronal cell proliferation. 34,35 In the present study, we found that PIKE is highly expressed in SCC cells and mediates EGFR-dependent SCC cell proliferation. RESULTS PIKE is highly expressed in human SCC cells but at a low level in normal human keratinocytes The SH3 domain of PLC-g1 has been found to activate nuclear PIKE that activates nuclear class Ia PI3K, which in turn, triggers signaling cascades mediating neuronal cell proliferation.…”
Section: Introductionsupporting
confidence: 51%
“…PI3-kinase was immunoprecipitated with rabbit anti-p110 from the cell extract, and washed with the following buffers: 3 times with buffer A (PBS, 1% NP-40, 1 mM dithiothreitol (DTT)); 2 times with buffer B (PBS, 0.5 M LiCl, 1 mM DTT); and 2 times with buffer C (10 mM Tris-HCl, pH 7.4, 0.1 M NaCl, 1 mM DTT). Subsequent steps were performed as described 12 .…”
Section: Pi 3-kinase Assaymentioning
confidence: 99%
“…PIKE activates PI 3-kinase in a GTP-dependent manner 11 . PLC-γ1 acts as a physiological guanine nucleotide exchange factor (GEF) for PIKE 12 . Recently, it has been shown that netrin-1 induces activation of PLC-γ1, which is mediated by DCC but not UNC5B or neogenin 24.…”
mentioning
confidence: 99%
“…In PC12 cells, NGF treatment elicits powerful anti-apoptotic signaling cascades [Patapoutian and Reichardt, 2001]. In response to NGF, PI-PLCg1 translocates to the nucleus where it acts as a physiological guanine-nucleotide-exchange factor for PIKE-S [Ye et al, 2002]. PIKE-S is a nuclear-specific GTPase that enhances PI3K activity and is regulated by protein 4.1N [Ye et al, 2000;Ye and Snyder, 2004].…”
Section: New Roles For Nuclear Pi3k Andmentioning
confidence: 99%